Tadris Maharah Al-Qiroah li An-Nathiqiin bi Ghairiha Al-Usus An-Nazhariah wa Al-Istiratijiyat At-Tathbiqiyah - Lahlali, Sanaa Allal (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
This research paper highlights the reading skill in teaching Arabic to other speakers as a receptive skill (listening-reading) that contributes to enriching the learner's language ammunition. The research is made up of two parts: a theoretical part: it focuses on the importance of reading skill, while presenting its types and the purpose of its teaching. And a practical one which deals with the most important strategies used while presenting a reading lesson. This research paper is based on theoretical ideas derived from the heart of applied linguistics, as well as from applied study based on, on the one hand, an educational experience that I have gained while teaching non-Arabic speakers from different countries and nationalities, as well as benefiting from some training courses developed by academic specialists in Arabic language education for nonnative speakers of Arabic.Â  On the other hand, it benefits from specialized and varied linguistic sources and references.ØªØ±ÙˆÙ… Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø§Ù„Ø¨ØØ«ÙŠØ© ØªØ³Ù„ÙŠØ· Ø§Ù„Ø¶ÙˆØ¡ Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ Ù…Ø¬Ø§Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§Ø› Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡Ø§ Ù…Ù† Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§Ø³ØªÙ‚Ø¨Ø§Ù„ÙŠØ© (Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹- Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©) Ø§Ù„ØªÙŠ ØªØ³Ù‡Ù… ÙÙŠ Ø¥ØºÙ†Ø§Ø¡ Ø§Ù„Ø°Ø®ÙŠØ±Ø© Ø§Ù„Ù„ØºÙˆÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ù…ØªØ¹Ù„Ù…. ÙˆÙŠØªÙƒÙˆÙ† Ø§Ù„Ø¨ØØ« Ù…Ù† Ø´Ù‚ÙŠÙ†: Ø´Ù‚ Ù†Ø¸Ø±ÙŠ: ØªØ·Ø±Ù‚ Ù„Ù…Ø§Ù‡ÙŠØ© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙˆØ£Ù‡Ù…ÙŠØªÙ‡Ø§ØŒ Ù…Ø¹ Ø¹Ø±Ø¶ Ø£Ù†ÙˆØ§Ø¹Ù‡Ø§ ÙˆØ§Ù„Ù‡Ø¯Ù Ù…Ù† ØªØ¯Ø±ÙŠØ³Ù‡Ø§. ÙˆØ´Ù‚ ØªØ·Ø¨ÙŠÙ‚ÙŠ ØªÙ… ÙÙŠÙ‡ Ø¹Ø±Ø¶ Ø£Ù‡Ù… Ø§Ù„Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ§Øª Ø§Ù„Ù…ØªØ¨Ø¹Ø© ÙÙŠ ØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©. ØªØ³ØªÙ†Ø¯ Ù‡Ø°Ù‡ Ø§Ù„ÙˆØ±Ù‚Ø© Ø§Ù„Ø¨ØØ«ÙŠØ© Ø¥Ù„Ù‰ Ø£ÙÙƒØ§Ø± Ù†Ø¸Ø±ÙŠØ© Ù…Ø³ØªÙ…Ø¯Ø© Ù…Ù† ØµÙ…ÙŠÙ… Ø§Ù„Ù„Ø³Ø§Ù†ÙŠØ§Øª Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ÙŠØ©ØŒ Ùˆ ÙˆØ¥Ù„Ù‰ Ø¯Ø±Ø§Ø³Ø© ØªØ·Ø¨ÙŠÙ‚ÙŠØ© Ù…ÙŠØ¯Ø§Ù†ÙŠØ© ØªØ±ØªÙƒØ² â€“ Ù…Ù† Ø¬Ù‡Ø© â€“ Ø¹Ù„Ù‰ ØªØ¬Ø±Ø¨Ø© ØªØ±Ø¨ÙˆÙŠØ© Ø®Ø¶Ù†Ø§Ù‡Ø§ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø¯ÙˆÙ„ ÙˆØ¬Ù†Ø³ÙŠØ§Øª Ù…Ø®ØªÙ„ÙØ©ØŒ ÙØ¶Ù„Ø§ Ø¹Ù† Ø§Ø³ØªÙØ§Ø¯ØªÙŠ â€“ ØØ¶ÙˆØ±ÙŠØ§ â€“ Ù…Ù† Ø¨Ø¹Ø¶ Ø§Ù„Ø¯ÙˆØ±Ø§Øª Ø§Ù„ØªØ¯Ø±ÙŠØ¨ÙŠØ© Ø§Ù„ØªÙŠ Ø£Ø·Ø±Ù‡Ø§ Ø®Ø¨Ø±Ø§Ø¡ Ø¯ÙˆÙ„ÙŠÙˆÙ†. ÙˆØªØ±ØªÙƒØ² Ù…Ù† Ø¬Ù‡Ø© Ø£Ø®Ø±Ù‰ Ø¹Ù„Ù‰ Ù…ØµØ§Ø¯Ø± ÙˆÙ…Ø±Ø§Ø¬Ø¹ Ù„Ø³Ø§Ù†ÙŠØ© Ù…ØªØ®ØµØµØ© ÙˆÙ…ØªÙ†ÙˆØ¹Ø©.Â